Propionic acidemia: gray matter disease meets subcortical leukodystrophy - Fels-Palesandro, Hannah; Hörster, Friederike; Haas, Dorothea; Gleich, Florian; Garbade, Sven; Kölker, Stefan; Harting, Inga (Journal of inherited metabolic disease, 2025)
Imaging literature on propionic acidemia (PA) is predominantly concerned with deep gray matter changes. In order to investigate the spectrum and patterns of MRI changes, 45 MRI scans of 13 patients (0.31-33.2 years) were systematically analyzed. Deep and cortical gray matter changes were associated with acute metabolic decompensation. Striatum was affected in 10/13; T2-hyperintensity was often mild, normalizing and becoming T2-hypointense in one patient each without movement disorder. Pallidum was T2-hyperintense in the 3 infants imaged for acute decompensation, with restricted diffusion in 2/3 and normalizing in 2/2 with follow-up. Dentate and thalamus were T2-hyperintense in 7/13 and 2/13, respectively, without resolution. Cerebellar watershed injury (4/13) and cortico-subcortical involvement with transiently restricted diffusion, T2/FLAIR-hyperintensity, and/or swelling (3/13) were more common with seizures during decompensation. A pattern of predominantly subcortical leukoencephalopathy was observed in 7/9 patients aged 9 years and above. Small foci of restricted diffusion, T2/FLAIR-hyperintensity, and variable T1-hypointensity evolved into bilateral, sometimes extensive changes with restricted and facilitated diffusion, decreasing in 3/6 with follow-up MRI at 14.7-19.5 years. Volume deficit was common, including a thin brainstem in 9/13. Predominantly subcortical white matter changes are a characteristic finding in older children with PA, might reflect microvacuolation, and may improve. Transient pallidal changes in infants with acute decompensation might represent myelin splitting during active myelination of white matter-rich pallidum. Cortico-subcortical changes and cerebellar watershed injury during acute metabolic decompensation were more likely with seizures; like the more common striatal involvement they occurred without age-predilection.
Online veröffentlicht: 4. November 2025
Gesehen am 21.01.2026